Low temperature slurry and heterojunction battery
Through the surface treatment of spherical silver powder and copper powder conductive powder and antioxidant at a ratio of 20:80-70:30, combined with ion accelerator, the filling of low-temperature slurry in fine-line printing and small-size velvet-making pyramid batteries is solved and the filling and filling of low-temperature slurry in fine-line printing and small-size velvet-making pyramid batteries and The contact problem has improved the photoelectric conversion efficiency and service life of heterojunction batteries.
Patent Information
- Application Number
- CN202211731942.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing low-temperature slurries have problems such as poor filling and high contact resistance in fine-line printing and small-size velvet-making pyramid heterojunction battery production, resulting in a decrease in photoelectric conversion efficiency.
Use spherical silver powder and copper powder of 20:80-70:30 as conductive powder, and after surface treatment of antioxidants and combined with ion accelerators, low-temperature slurry with low resistivity and good adhesion, suitable for extremely narrow Screen printing of open screen and small size velvet pyramids.
The high conductivity and printing matching of the slurry are achieved, the production cost of heterojunction batteries is reduced, and the photoelectric conversion efficiency and service life of the battery are improved.
Smart Images

Figure CN116052923B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery slurry manufacturing, and in particular to a low-temperature slurry and a heterojunction battery. Background Art
[0002] Under the current situation of high cost of metallization of heterojunction batteries, the demand for cost reduction on the production side is becoming increasingly strong. Fine-line printing is the only way to reduce the cost of photovoltaic printing. The existing battery silver paste uses flaky silver powder in the paste, and the average particle size is controlled at 3-5μm. At present, low-temperature paste printing generally uses a screen with an opening of 28-35 microns and a mesh of 430 mesh. For PERC paste, a screen with an opening of 14-16 microns and a mesh of 520 mesh are currently used in batches. However, due to the poor rolling and mesh-passing properties of the flaky powder in the low-temperature paste, the low-temperature paste using flaky powder as filler has poor matching in fine-line printing, and the probability of virtual printing and broken grids is greatly increased.
[0003] Due to the need to improve the efficiency of heterojunction cells, the requirements for light trapping are gradually increasing, so the size of the pyramid has been reduced from 3-5μm to the current 1-3μm in texturing. For 1-3μm texturing pyramids, there is a high probability that the 3-5 micron flaky silver powder will not be able to fill the bottom of the pyramid well. The flaky silver powder may be like a bridge on the top of the two pyramids, resulting in no silver powder filling at the bottom of the pyramid, greatly increasing the contact resistance, and ultimately leading to a decrease in photoelectric conversion efficiency. Summary of the invention
[0004] In order to solve the above problems, the purpose of the present invention is to provide a low-temperature slurry and a heterojunction battery. The low-temperature slurry provided by the present invention has low resistivity and good adhesion after curing, and is suitable for the production process of heterojunction batteries for fine-line printing and small-size pyramids, which can improve the electrical performance of heterojunction batteries while reducing costs.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a conductive powder, which comprises a first metal powder and a second metal powder in a weight ratio of 20:80-70:30; the first metal powder is a spherical powder, the average particle size of the first metal powder is 1-3 μm, and the tap density is above 4.5 g / cc; the second metal powder is a spherical powder, the average particle size of the second metal powder is 0.1-1.5 μm, and the tap density is above 3.5 g / cc; the first metal powder is the first metal powder surface-treated with an antioxidant; and the second metal powder is the second metal powder surface-treated with an antioxidant.
[0006] The above-mentioned conductive powder provided by the present invention is a spherical metal powder with a small particle size, which can match the industrial batch screen printing with an extremely narrow opening screen with an opening of less than 20μm, solving the large slurry consumption and high cost in the production process of heterojunction batteries, as well as the filling and contact problems of the current small pyramids in the production of velvet.
[0007] In the above-mentioned conductive powder, if there are too many spherical powders with large particle sizes, although the conductivity is improved, it will lead to a decrease in the printability of the slurry, and it will also have an adverse effect on the adhesion of the cured product; if there are too many spherical powders with small particle sizes, although the printability will be improved, it will lead to an increase in the viscosity and resistivity of the slurry, and ultimately affect the electrical performance of the battery. The present invention has found that by controlling the weight ratio of the first metal powder surface-treated with an antioxidant to the second metal powder to 20:80-70:30, a slurry with both high conductivity and high printability can be obtained. Furthermore, the weight ratio of the first metal powder to the second metal powder can be controlled to 25:75-70:30, 30:70-60:40.
[0008] According to a specific embodiment of the present invention, the D10 particle size of the conductive powder is generally 0.3-0.9 μm, and can be further controlled to be 0.5-0.8 μm.
[0009] According to a specific embodiment of the present invention, the D50 particle size of the conductive powder is 1.2-3.0 μm, and can be further controlled to be 1.3-2.0 μm.
[0010] According to a specific embodiment of the present invention, the D90 particle size of the conductive powder is 2.5-6 μm, and can be further controlled to be 3-4 μm.
[0011] In the above-mentioned conductive powder, the surface treatment of the first metal powder and the second metal powder with an antioxidant can not only inhibit the oxidation of the metal powder, but also passivate the ability of the variable valence ions, thereby inhibiting the migration of metal ions and improving the service life of the heterojunction battery assembly. The antioxidant includes one or a combination of two or more of 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-p-cresol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, N,N'-hexamethylenebis-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanate, 4-hydroxydodecanoic acid anilide, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and dioctadecyl pentaerythritol diphosphite.
[0012] In a specific embodiment of the present invention, the surface treatment method can be a chemical treatment method, specifically comprising: dispersing the untreated first metal powder or the second metal powder in a surface treatment liquid, and drying to obtain the first metal powder with an antioxidant coated on the surface or the second metal powder with an antioxidant coated on the surface; wherein the surface treatment liquid contains an antioxidant. The surfaces of the first metal powder and the second metal powder can be coated with an antioxidant to achieve surface modification of the first metal powder and the second metal powder.
[0013] In the above surface treatment method, the mass ratio of the above untreated first metal powder to the antioxidant is usually controlled to be (5-21): (14-83), and the mass ratio of the untreated second metal powder to the antioxidant is usually (5-21): (14-83). In some specific embodiments, the dispersion method can be ultrasonic, and the ultrasonic dispersion time can be controlled to be 20-60 minutes. The drying conditions can specifically be: vacuum drying for 1-2 hours, and the drying temperature is 60-90°C.
[0014] In the above antioxidant solution, the mass ratio of the antioxidant to the surface treatment liquid can be generally controlled to be (14-83): 100. The solvent used in the surface treatment liquid can include one or a combination of two or more of acetone, ethyl acetate, butyl acetate, ethanol, isopropanol, etc. Further, the surface treatment liquid can also include a coupling agent, and the coupling agent can include one or a combination of two or more of aminopropyl triethoxysilane, aminopropyl trimethoxysilane, glycidyl methoxypropyl trimethoxysilane, n-octyl triethoxysilane, vinyl triethoxysilane, vinyl-tri(2-methoxyethoxy) silane, isopropyl trioleyl titanate, isopropoxy tri(dodecylbenzenesulfonyloxy) titanate, isopropoxy tri(dioctyl pyrophosphate acyloxy) titanate, bis(dioctyl pyrophosphate acyloxy) ethylene titanate, isopropyl tristearate titanate, isopropyl distearate acyloxy aluminate, etc.
[0015] In the above conductive powder, the first metal powder and the second metal powder independently include one or a combination of two or more of silver powder, copper powder, silver-coated copper powder, silver-coated nickel powder, and silver-coated aluminum powder. Further, the first metal powder may be silver-coated copper powder, and the second metal powder may be one of copper powder, silver powder, or silver-coated copper powder.
[0016] The present invention also provides a low-temperature slurry, the raw materials of which include, by weight: 3-8 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter, and the above-mentioned conductive powder provided by the present invention; wherein the conductive powder includes 20-70 parts of the above-mentioned first metal powder (surface treated) and 30-80 parts of the above-mentioned second metal powder (surface treated).
[0017] In the above-mentioned low-temperature slurry, compared with the existing low-temperature slurry using flaky powder, the present invention uses spherical metal powder as the conductive powder to reduce the size of the conductive powder, but it will also cause the resistivity of the low-temperature slurry to increase. In this regard, the present invention further adds a certain ion promoter to the low-temperature slurry to cooperate with the conductive powder to reduce the contact resistance of the slurry. After the resin in the low-temperature slurry is cured, the ion promoter can carry out electron transmission, greatly reducing the resistivity of the resin, thereby reducing the overall resistivity of the low-temperature slurry. Furthermore, the reduction in the resistivity of the resin will reduce the interface resistance of the cured slurry in contact with the heterojunction battery TCO, thereby obtaining a higher battery light conversion efficiency.
[0018] According to a specific embodiment of the present invention, the weight ratio of the first metal powder, the second metal powder and the thermosetting resin can be controlled to be 25-70:30-75:3-8. That is, in parts by weight, the raw materials of the low-temperature slurry include: conductive powder, 3-8 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter; wherein the conductive powder includes 25-70 parts of the first metal powder and 30-75 parts of the second metal powder.
[0019] According to a specific embodiment of the present invention, the weight ratio of the first metal powder, the second metal powder and the thermosetting resin can be controlled to be 30-60:40-70:3-8. That is, in parts by weight, the raw materials of the low-temperature slurry include: conductive powder, 3-8 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter; wherein the conductive powder includes 30-60 parts of the first metal powder and 40-70 parts of the second metal powder.
[0020] According to a specific embodiment of the present invention, the weight ratio of the thermosetting resin to the ion promoter can be further controlled to be 2-6: 0.02-0.2, 3-6.5: 0.02-0.2, 3-7: 0.02-0.2, 3-7.5: 0.02-0.2. That is, in parts by weight, the raw materials of the low-temperature slurry can include: conductive powder, 2-6 parts or 3-6.5 parts or 3-7 parts or 3-7.5 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter; the conductive powder includes 20-70 parts of the first metal powder and 30-80 parts of the second metal powder.
[0021] According to a specific embodiment of the present invention, the weight ratio of the solvent to the ion promoter can be further controlled to be 3-5:0.02-0.2. That is, in parts by weight, the raw materials of the low-temperature slurry can include: conductive powder, 3-8 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-5 parts of solvent, 0.02-0.2 parts of ion promoter; the conductive powder includes 20-70 parts of the first metal powder and 30-80 parts of the second metal powder.
[0022] In the above low-temperature slurry, the ion promoter includes one or a combination of two or more of octadecyl hydroxyethyl dimethylamine nitrate, stearyl trimethyl ammonium chloride, lauryl amide propyl trimethyl ammonium, alkyl sulfonates, alkyl sulfates, alkyl phosphates, alkylphenol polyoxyethylene ether sulfates, etc. Among them, octadecyl hydroxyethyl dimethylamine nitrate can be octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, alkyl sulfates can include triethanolamine dodecyl sulfate, and alkyl phosphates can include octadecyl phosphate.
[0023] In the above-mentioned low-temperature slurry, the thermosetting resin generally includes epoxy resin and / or polybutadiene resin, etc. The epoxy resin may specifically include one or a combination of two or more of bisphenol F epoxy resin, bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin, polycyanate triglycerol epoxy resin, amino-terminated liquid nitrile rubber, etc.
[0024] In the low-temperature slurry, the number average molecular weight of the epoxy resin is 1000-1500.
[0025] According to a specific embodiment of the present invention, the weight ratio of the epoxy resin to the polybutadiene resin can be controlled to be 2-6:1-2, for example, 2-5:1-2, 2-6:1-1.5, 2-5:1-1.5, etc.
[0026] According to a specific embodiment of the present invention, the raw materials of the low-temperature slurry may specifically include, by weight: 2-6 parts or 2-5 parts of epoxy resin, 1-2 parts or 1-1.5 parts of polybutadiene resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter, and the above-mentioned conductive powder provided by the present invention; wherein, the conductive powder includes 20-70 parts of the above-mentioned first metal powder (surface treated) and 30-80 parts of the above-mentioned second metal powder (surface treated).
[0027] In the above-mentioned low-temperature slurry, the coupling agent includes a titanate coupling agent and / or an organosilicon coupling agent, etc. Specifically, the titanate coupling agent may include one or a combination of two or more of isopropyl trititanate, isopropyl dioleyl titanate, monoalkoxy unsaturated fatty acid titanate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate (FT201), etc.; the organosilicon coupling agent may include one or a combination of two or more of 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-[(2,3)-glycidoxy]propyl methyl dimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, N-aminoethyl-3-aminopropyl methyl dimethoxysilane, γ-glycidyl ether oxypropyl trimethoxysilane (KH560), etc.
[0028] In the above-mentioned low-temperature slurry, the curing agent includes one or a combination of two or more of boron trifluoride-monoethylamine complex, 2-methylimidazole, dicyandiamide, modified fatty amine, aromatic diamine, etc.
[0029] In the above low-temperature slurry, the solvent includes one or a combination of two or more of terpineol, butyl carbitol, butyl carbitol acetate, ethylene glycol acetate, ethylene glycol butyl ether, ethylene glycol, propylene glycol, dibutyl diglycol, glycol ether, tributyl citrate, dibutyl phthalate, etc.
[0030] The present invention also provides a heterojunction battery, wherein the conductive film and / or conductive electrode of the heterojunction battery is formed by solidifying the above-mentioned low-temperature slurry.
[0031] The beneficial effects of the present invention are:
[0032] 1. The conductive powder and low-temperature slurry provided by the present invention can be applied to batch screen printing of industrial ultra-narrow opening screens and small-sized texturing pyramids, effectively solving the problems of large slurry consumption and high cost in the production process of heterojunction batteries, as well as the filling and contact problems of the current small-sized texturing pyramids.
[0033] 2. The low-temperature slurry provided by the present invention can be thermally cured at a low temperature environment below 200°C, and the conductive film or conductive electrode after the low-temperature slurry is completely cured has low resistivity and good adhesion, which can further improve the photoelectric conversion efficiency of the heterojunction battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the laser particle size distribution diagram of the conductive powder of Example 1, Example 3, and Example 4.
[0035] Figure 2 This is the laser particle size distribution diagram of the conductive powder of Example 2, Example 5, Example 8, and Example 9.
[0036] Figure 3 This is the laser particle size distribution diagram of the conductive powder of Example 6.
[0037] Figure 4 This is the laser particle size distribution diagram of the conductive powder of Example 7.
[0038] Figure 5 This is a SEM image of 1-3 micron pyramids.
[0039] Figure 6 This is a SEM image of a 3-5 micron pyramid. DETAILED DESCRIPTION
[0040] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.
[0041] In the following examples and comparative examples, the manufacturer of the octadecyl hydroxyethyl dimethylamine nitrate used is Jiangsu Haian Petrochemical, and the model is antistatic agent SN (octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate). The titanate coupling agent is FT201, and the silicone coupling agent is KH560.
[0042] Example 1
[0043] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0044] 38 parts of the first metal powder, 50 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 1 part of titanate coupling agent, 2 parts of pineol, 2 parts of tributyl citrate, 1.45 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.05 parts of octadecylhydroxyethyldimethylamine nitrate.
[0045] The first metal powder and the second metal powder constitute the conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.8 μm and a tap density of 4.8 g / cc. The second metal powder is spherical silver powder with an average particle size of 1.3 μm and a tap density of 3.5 g / cc.
[0046] The first metal powder is surface treated by mixing the untreated first metal powder with the surface treatment liquid in a mass ratio of 7:100, ultrasonically dispersing for 50 minutes, and vacuum drying at 80°C for 1.5 hours to obtain the first metal powder coated with an antioxidant.
[0047] The surface treatment liquid is formed by mixing 2,2-methylenebis(4-methyl-6-tert-butylphenol), isopropyl tristearate titanate and isopropyl alcohol in a mass ratio of 12:5:83.
[0048] The second metal powder is also a surface-treated second metal powder, and its surface treatment method (including steps and parameters) is the same as the surface treatment method of the first metal powder.
[0049] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0050] Example 2
[0051] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0052] 38 parts of the first metal powder, 50 parts of the second metal powder, 1.5 parts of bisphenol F epoxy resin, 1.3 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.0 parts of polybutadiene resin, 1 part of titanate coupling agent, 2 parts of pineol, 2 parts of tributyl citrate, 1.4 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.1 parts of octadecylhydroxyethyldimethylamine nitrate.
[0053] The first metal powder and the second metal powder constitute conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.5 μm and a tap density of 4.9 g / cc or more. The second metal powder is spherical silver powder with an average particle size of 1.1 μm and a tap density of 3.7 g / cc.
[0054] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0055] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0056] Example 3
[0057] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0058] 38 parts of the first metal powder, 50 parts of the second metal powder, 1.5 parts of bisphenol A epoxy resin, 1.3 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.0 parts of polybutadiene resin, 1 part of titanate coupling agent, 2 parts of pineol, 1.8 parts of tributyl citrate, 1.4 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.2 parts of octadecylhydroxyethyldimethylamine nitrate.
[0059] The first metal powder and the second metal powder constitute the conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.8 μm and a tap density of 4.8 g / cc. The second metal powder is spherical silver powder with an average particle size of 1.3 μm and a tap density of 3.5 g / cc.
[0060] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0061] The number average molecular weight of bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0062] Example 4
[0063] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0064] 38 parts of the first metal powder, 50 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanurate triglyceride epoxy resin, 1.5 parts of amino-terminated liquid nitrile rubber, 1 part of titanate coupling agent, 2 parts of pine alcohol, 1.9 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.1 parts of triethanolamine dodecyl sulfate.
[0065] The first metal powder and the second metal powder constitute the conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.8 μm and a tap density of 4.8 g / cc. The second metal powder is spherical silver powder with an average particle size of 1.3 μm and a tap density of 3.5 g / cc.
[0066] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0067] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin, polycyanate triglycerol epoxy resin and amino-terminated liquid nitrile rubber is 1000-1500.
[0068] Example 5
[0069] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0070] 38 parts of the first metal powder, 50 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 0.5 parts of titanate coupling agent, 1 part of silicone coupling agent, 1.5 parts of pinene alcohol, 1.8 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.2 parts of triethanolamine dodecyl sulfate.
[0071] The first metal powder and the second metal powder constitute conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.5 μm and a tap density of 4.9 g / cc or more. The second metal powder is spherical silver powder with an average particle size of 1.1 μm and a tap density of 3.7 g / cc.
[0072] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0073] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0074] Example 6
[0075] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0076] 20 parts of the first metal powder, 68 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanurate triglycerol epoxy resin, 1.5 parts of amino-terminated liquid nitrile rubber, 1 part of titanate coupling agent, 2 parts of pineol, 1.9 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.1 parts of triethanolamine dodecyl sulfate.
[0077] The first metal powder and the second metal powder constitute the conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.8 μm and a tap density of 4.8 g / cc. The second metal powder is spherical silver powder with an average particle size of 1.3 μm and a tap density of 3.5 g / cc.
[0078] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0079] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0080] Example 7
[0081] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0082] 20 parts of the first metal powder, 68 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 0.5 parts of titanate coupling agent, 1 part of silicone coupling agent, 1.5 parts of pinene alcohol, 1.8 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.2 parts of triethanolamine dodecyl sulfate.
[0083] The first metal powder and the second metal powder constitute conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.5 μm and a tap density of 4.9 g / cc or more. The second metal powder is spherical silver powder with an average particle size of 1.1 μm and a tap density of 3.7 g / cc.
[0084] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0085] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0086] Example 8
[0087] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0088] 38 parts of the first metal powder, 50 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 0.5 parts of titanate coupling agent, 1 part of silicone coupling agent, 1.5 parts of pinene alcohol, 1.8 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.2 parts of lauramide propyl trimethylammonium.
[0089] The first metal powder and the second metal powder constitute conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.5 μm and a tap density of 4.9 g / cc or more. The second metal powder is spherical silver powder with an average particle size of 1.1 μm and a tap density of 3.7 g / cc.
[0090] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0091] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0092] Example 9
[0093] This embodiment provides a low-temperature slurry. The raw materials of the low-temperature slurry include, by weight:
[0094] 38 parts of the first metal powder, 50 parts of the second metal powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 0.5 parts of titanate coupling agent, 1 part of silicone coupling agent, 1.5 parts of pinene alcohol, 1.8 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, 0.2 parts of boron trifluoride-monoethylamine complex, and 0.2 parts of octadecyl phosphate.
[0095] The first metal powder and the second metal powder constitute conductive powder. The first metal powder is spherical copper-coated silver powder with an average particle size of 2.5 μm and a tap density of 4.9 g / cc or more. The second metal powder is spherical silver powder with an average particle size of 1.1 μm and a tap density of 3.7 g / cc.
[0096] The first metal powder and the second metal powder are respectively subjected to surface treatment, and the surfaces are coated with the antioxidant 2,2-methylenebis(4-methyl-6-tert-butylphenol). The specific surface treatment method is the same as that in Example 1.
[0097] The number average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0098] Comparative Example 1
[0099] This comparative example provides a low-temperature slurry, and the raw materials of the low-temperature slurry include, by weight:
[0100] 38 parts of the first spherical silver powder, 50 parts of the second spherical silver powder, 0.5 parts of bisphenol F epoxy resin, 1.8 parts of resorcinol formaldehyde epoxy resin, 1.5 parts of polycyanate triglycerol epoxy resin, 1.5 parts of polybutadiene resin, 1 part of titanate coupling agent, 2 parts of pineol, 2 parts of tributyl citrate, 1.5 parts of dibutyl phthalate, and 0.2 parts of boron trifluoride-monoethylamine complex.
[0101] The first spherical silver powder and the second spherical silver powder constitute the conductive powder. The first spherical silver powder has an average particle size of 2.9 μm and a tap density of 4.2 g / cc or more. The second spherical silver powder has an average particle size of 1.5 μm and a tap density of 3.6 g / cc or more. Both silver powders are not surface treated.
[0102] The average molecular weight of bisphenol F epoxy resin, resorcinol formaldehyde epoxy resin and polycyanurate triglycerol epoxy resin is 1000-1500.
[0103] The particle size distribution of the conductive powder used in the low temperature slurry of Examples 1 to 9 was characterized. Figures 1 to 4 shown.
[0104] The conductive powders used in Example 1, Example 3 and Example 4 are exactly the same. Figure 1 : is the laser particle size distribution diagram of the conductive powder of Example 1, Example 3, and Example 4. Figure 1 It can be seen that the D10 particle size of the conductive powder is 0.861 μm, the D50 particle size is 2.078 μm, and the D90 particle size is 4.331 μm.
[0105] The conductive powders used in Examples 2, 5, 8 and 9 are exactly the same. Figure 2 The laser particle size distribution diagram of the conductive powder of Example 2, Example 5, Example 8 and Example 9. Figure 2 It can be seen that the D10 particle size of the conductive powder is 0.618 μm, the D50 particle size is 1.522 μm, and the D90 particle size is 3.501 μm.
[0106] Figure 3 This is the laser particle size distribution diagram of the conductive powder of Example 6. Figure 3 It can be seen that the D10 particle size of the conductive powder is 0.605 μm, the D50 particle size is 1.366 μm, and the D90 particle size is 3.251 μm.
[0107] Figure 4 This is the laser particle size distribution diagram of the conductive powder of Example 7. Figure 4 It can be seen that the D10 particle size of the conductive powder is 0.605 μm, the D50 particle size is 1.375 μm, and the D90 particle size is 2.860 μm.
[0108] Test Example 1
[0109] The performance of the low-temperature slurries of Examples 1 to 9 and Comparative Example 1 was tested. The low-temperature slurries to be tested were tested on batteries whose TCO substrates were ITO (97:3), ITO (90:10), IWO, and ICO, respectively. The slurries were screen-printed on the substrates and dried and cured at 200°C to obtain testable silver electrode grid lines, and the viscosity, resistivity, contact resistance, etc. of the slurries were measured. The performance test methods are as follows:
[0110] 1. Viscosity test method:
[0111] The conductive paste was used as a sample and the viscosity test was performed using a Brookfield viscometer. 1) When the rotation speed was 1 r / min, the reading time was 60 s; 2) When the rotation speed was 10 r / min, the reading time was 4 min; 3) When the rotation speed was 100 r / min, the reading time was 60 s. The viscosity of the conductive paste at different rotation speeds was measured.
[0112] 2. Resistivity test: Use a four-probe ohmmeter to test the resistance at both ends of the electrode. The electrode is a heterojunction battery formed by a TCO substrate printed with a conductive paste. The specific measurement process is: use a resistor to test the resistance between two points, and then use a 3D microscope to test the width and height of the main grid, and calculate the resistivity result according to the following formula:
[0113] Resistivity = resistance / busbar width × busbar height.
[0114] 3. Contact resistance: (1) Print a specific pattern on the heterojunction cell and dry it to solidify; (2) Use a laser slicer to cut out a cell of a specified size in the printed pattern area; (3) Use a contact resistance device to measure the contact resistance.
[0115] 4. Textile pyramid: The morphology of the textile pyramid was characterized by scanning electron microscopy (SEM). The sizes of the textile pyramids were measured to be 1-3μm and 3-5μm respectively. Figure 5 , Figure 6 shown.
[0116] The test data of the low temperature slurry in the above examples are summarized in Table 1 and Table 2. The contact resistance in Table 1 is tested when the texturing pyramid is 3-5 μm; the contact resistance in Table 2 is tested when the texturing pyramid is 1-3 μm.
[0117] Table 1
[0118]
[0119] Table 2
[0120]
[0121] As can be seen from Table 1, the low-temperature slurry of Comparative Example 1 without adding an ion promoter has a higher resistivity and contact resistance; while the low-temperature slurries of Examples 1 and 2 with added ion promoters have significantly reduced resistivity and contact resistance. Example 3 increases the amount of ion promoter added on the basis of Examples 1 and 2, and the resistivity and contact resistance of the obtained low-temperature slurry are increased instead; Examples 5, 8 and 9 prove that the performance of the slurry can be adjusted by adjusting the type of ion promoter.
[0122] Compared with Comparative Example 1, ion promoters were added in Examples 4 and 5, and the resistivity and contact resistance of the low-temperature slurry further decreased with the increase of the added amount.
[0123] It can be seen from Table 2 that after the size of the texturing pyramid is changed from 3-5μm to 1-3μm, the contact resistance of Comparative Example 1 increases significantly, and the photoelectric conversion efficiency is greatly affected; while the contact resistance of each embodiment decreases, indicating that the low-temperature slurry provided by the present invention is suitable for heterojunction batteries with small-sized texturing pyramids, and can reduce the contact resistance of the battery, effectively improving the photoelectric conversion efficiency.
Claims
1. A conductive powder comprising a first metal powder and a second metal powder in a weight ratio of 20:80-70:30; The first metal powder is a spherical powder, the average particle size of the first metal powder is 1-3 μm, and the tap density is greater than 4.5 g / cc; The second metal powder is a spherical powder, the average particle size of the second metal powder is 0.1-1.5 μm, and the tap density is greater than 3.5 g / cc; The first metal powder is a first metal powder that has been surface treated with an antioxidant; the second metal powder is a second metal powder that has been surface treated with an antioxidant; The antioxidant includes one or a combination of two or more of 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-p-cresol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, N,N'-hexamethylenebis-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanate, 4-hydroxydodecanoic acid anilide, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and dioctadecyl pentaerythritol diphosphite; The first metal powder and the second metal powder independently include one or a combination of two or more of silver powder, copper powder, silver-coated copper powder, silver-coated nickel powder and silver-coated aluminum powder.
2. The conductive powder according to claim 1, wherein The weight ratio of the first metal powder to the second metal powder is 25:75-70:
30.
3. The conductive powder according to claim 2, wherein: The weight ratio of the first metal powder to the second metal powder is 30:70-60:
40.
4. The conductive powder according to claim 1, wherein The D10 particle size of the conductive powder is 0.3-0.9 μm, the D50 particle size of the conductive powder is 1.2-3.0 μm, and the D90 particle size of the conductive powder is 2.5-6 μm.
5. The conductive powder according to claim 4, wherein The D10 particle size of the conductive powder is 0.5-0.8 μm.
6. The conductive powder according to claim 4, wherein The D50 particle size of the conductive powder is 1.3-2.0 μm.
7. The conductive powder according to claim 4, wherein The D10 particle size of the conductive powder is 3-4 μm.
8. The conductive powder according to claim 1, wherein The first metal powder is silver-coated copper powder, and the second metal powder is one of copper powder, silver powder or silver-coated copper powder.
9. The conductive powder according to any one of claims 1 to 8, wherein: The conductive powder can be used in the production process of heterojunction cells with 1 μm-3 μm textured pyramids.
10. A low-temperature slurry, wherein the raw materials of the low-temperature slurry include, by weight: 3-8 parts of thermosetting resin, 1-2 parts of coupling agent, 0.1-0.3 parts of curing agent, 3-6 parts of solvent, 0.02-0.2 parts of ion promoter, and the conductive powder according to any one of claims 1 to 9; Wherein, the conductive powder comprises 20-70 parts of a first metal powder and 30-80 parts of a second metal powder; The ion promoter includes one or a combination of two or more of octadecylhydroxyethyldimethylamine nitrate, stearyltrimethylammonium chloride, lauramidepropyltrimethylammonium, alkyl sulfonates, alkyl sulfates, alkyl phosphates, and alkylphenol polyoxyethylene ether sulfates.
11. The low-temperature slurry according to claim 10, wherein: The weight ratio of the first metal powder, the second metal powder and the thermosetting resin is 25-70:30-75:3-8.
12. The low-temperature slurry according to claim 11, wherein: The weight ratio of the first metal powder, the second metal powder and the thermosetting resin is 30-60:40-70:3-8.
13. The low-temperature slurry according to claim 10, wherein: The alkyl sulfates include triethanolamine lauryl sulfate; The alkyl phosphates include octadecyl phosphate.
14. The low-temperature slurry according to claim 10, wherein: The thermosetting resin includes epoxy resin and / or polybutadiene resin.
15. The low-temperature slurry according to claim 14, wherein: The weight ratio of the epoxy resin to the polybutadiene resin is 2-6:1-2.
16. The low-temperature slurry according to claim 14, wherein: The epoxy resin includes one or a combination of two or more of bisphenol F epoxy resin, bisphenol A epoxy resin, resorcinol formaldehyde epoxy resin, polycyanate triglycerol epoxy resin, and amino-terminated liquid nitrile rubber.
17. The low-temperature slurry according to claim 14, wherein: The number average molecular weight of the epoxy resin is 1000-1500.
18. The low-temperature slurry according to claim 10, wherein: The coupling agent is a titanate coupling agent and / or an organosilicon coupling agent.
19. The low-temperature slurry according to claim 18, wherein: The titanate coupling agent includes one or a combination of two or more of isopropyl trititanate, isopropyl dioleyl titanate, monoalkoxy unsaturated fatty acid titanate, and isopropyl tri(dioctyl pyrophosphate acyloxy) titanate.
20. The low-temperature slurry according to claim 18, wherein: The organic silicon coupling agent includes one or a combination of two or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
21. The low-temperature slurry according to claim 10, wherein: The curing agent includes one or a combination of two or more of boron trifluoride-monoethylamine complex, 2-methylimidazole, dicyandiamide, modified fatty amine, and aromatic diamine.
22. The low-temperature slurry according to claim 10, wherein: The solvent includes one or a combination of two or more of terpineol, butyl carbitol, butyl carbitol acetate, ethylene glycol acetate, ethylene glycol butyl ether, ethylene glycol, propylene glycol, dibutyl diglycol, glycol ether, tributyl citrate, and dibutyl phthalate.
23. The low-temperature slurry according to any one of claims 10 to 22, wherein: The low temperature slurry can be used in the production process of heterojunction cells with 1 μm-3 μm texturing pyramids.
24. A heterojunction battery, wherein a conductive film and / or a conductive electrode of the heterojunction battery is formed by curing the low-temperature slurry according to any one of claims 10 to 23.
25. The heterojunction battery according to claim 24, wherein: The heterojunction cell has texturing pyramids of 1-3 μm.
Citation Information
Patent Citations
Low-temperature conductive silver paste for solar heterojunction cell and preparation method of low-temperature conductive silver paste
CN115132403A
Low-cost silver-coated copper slurry for solar heterojunction cell and preparation method of low-cost silver-coated copper slurry
CN115206584A